2005
DOI: 10.1111/j.1365-2222.2005.02239.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric administration of Mycobacterium vaccae inhibits severe pulmonary allergic inflammation in a mouse model

Abstract: This is the first report to suggest that heat-killed mycobacteria can down-regulate symptoms of allergic inflammation by the intragastric route. These data suggest an alternative route of treatment with M. vaccae for patients with allergic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 29 publications
4
36
1
1
Order By: Relevance
“…There have been a few reports about the 8-isoprostane level of the EBC in moderate asthma patients [11, 26] or the 8-isoprostane level of EBC in mild asthma patients. The level of 8-isoprostane in mild asthma was reported to range from 10 to 20 pg/ml [28, 29]. We could not exclude the effect of ICS treatment on the level of 8-isoprostane in the present study compared with previous reports, and it will be necessary to measure 8-isoprostane in EBC from more moderate asthma patients.…”
Section: Discussioncontrasting
confidence: 50%
“…There have been a few reports about the 8-isoprostane level of the EBC in moderate asthma patients [11, 26] or the 8-isoprostane level of EBC in mild asthma patients. The level of 8-isoprostane in mild asthma was reported to range from 10 to 20 pg/ml [28, 29]. We could not exclude the effect of ICS treatment on the level of 8-isoprostane in the present study compared with previous reports, and it will be necessary to measure 8-isoprostane in EBC from more moderate asthma patients.…”
Section: Discussioncontrasting
confidence: 50%
“…Following two further immunizations with allergen, mice were challenged by the intratracheal route 40 days after the intragastric dose of M. vaccae. Interestingly, M. vaccae was as effective by this route as it was by the subcutaneous route, and at precisely the same doses (Hunt et al, 2005). Since much of an oral dose must be lost, this implies that the oral route is particularly efficient, in agreement with the observations that mycobacteria are easily picked up by M cells on Peyer's patches (Fujimura, 1986) and that the gut may be a major site of induction of RegT (Powrie et al, 2003).…”
Section: Vaccae By the Oral Routesupporting
confidence: 53%
“…It was also shown that intragastric administration of M. vaccae inhibited pulmonary allergic inflammation in murine models with increased production of IL-10 and IFN-γ [35]. In the agreement with these findings, we showed that OVA induced IL-10 levels tended to be higher in the M. vaccae/OVA group compared to other groups.…”
Section: Discussionsupporting
confidence: 81%
“…Hunt et al showed that a single intragastric administration of M. vaccae in mice induced a transient increase in the production of IL-10 and IFN-γ by mesenteric lymph nodes and splenocytes [35]. In addition Zuany-Amorim et al demonstrated that killed M. vaccae gives rise to allergen-specific CD4 + CD45RB Lo regulatory T cells, which were able to protect from airway inflammation in OVA-sensitized mice [40].…”
Section: Discussionmentioning
confidence: 99%